2013
DOI: 10.1136/flgastro-2013-100318
|View full text |Cite
|
Sign up to set email alerts
|

Reversible khat-induced hepatitis: two case reports and review of the literature

Abstract: Recreational chewing of Catha edulis (khat) leaves is part of the ethnic culture of Somali, Yemeni and other East African societies for its stimulant properties. With increasing emigration, khat use has become common in these ethnic groups once they move to other areas such as Europe and the USA; one-third of the UK Somali population report khat use within the last month. Cathinone, the active component of the khat leaves, is controlled under the UK Misuse of Drugs Act, but the use of the khat plant and its le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…The mechanism of khat-associated hepatotoxicity is not well elucidated, though animal studies demonstrate fibrosis and liver injury with chronic use [4]. The injury is typically hepatocellular causing raised transaminase enzymes and has in some cases induced an autoimmune hepatitis wherein autoantibodies develop [5]. Resolution of the hepatitis typically occurs with cessation of use; however, there are some reports of patients developing severe acute hepatitis resulting in death or requiring liver transplantation [4, 6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism of khat-associated hepatotoxicity is not well elucidated, though animal studies demonstrate fibrosis and liver injury with chronic use [4]. The injury is typically hepatocellular causing raised transaminase enzymes and has in some cases induced an autoimmune hepatitis wherein autoantibodies develop [5]. Resolution of the hepatitis typically occurs with cessation of use; however, there are some reports of patients developing severe acute hepatitis resulting in death or requiring liver transplantation [4, 6].…”
Section: Discussionmentioning
confidence: 99%
“…Resolution of the hepatitis typically occurs with cessation of use; however, there are some reports of patients developing severe acute hepatitis resulting in death or requiring liver transplantation [4, 6]. Several other case reports have been published, implicating khat use in acute hepatitis cases in Somalian immigrants [5, 7, 8]. Patients typically presented after years of use, but some cases presented after chewing for only a few weeks.…”
Section: Discussionmentioning
confidence: 99%
“…The histopathological study of their liver tissues revealed marked lobular hepatitis with no fibrosis in case 1, wherein case 2, fibrosis was evident. Both patients improved on khat cessation [12].…”
Section: Khat Associated Acute Liver Injury Chronic Hepatitis and Cmentioning
confidence: 98%
“…All protests began after the restarting of khat chewing. He was again advised to abstain from khat, and his LFTs improved gradually over eight weeks, returning to normal in six months [ 29 ].…”
Section: Reviewmentioning
confidence: 99%
“…He re-presented five months later with another acute hepatitis following an episode of khat chewing. High liver enzymes were noted and adverse viral profile; a liver magnetic resonance imaging (MRI) was done, which showed further reduction in the size of the left lobe of the liver with new fibrosis in the right lobe [ 29 ]…”
Section: Reviewmentioning
confidence: 99%